Site factors and attract foreign direct investment Indian software industry as a model - Mustapha Belmokadem; Ali Yousfat (Dirassat Journal Economic Issue, 2010)
The article aims to study situational factors and their relationship to attracting foreign direct investment in light of globalization and openness, by choosing the Indian software industry as a model for the study.